Strategy For Developing Micro Small And Medium Enterprises Based On Creative Economy In Faiz Convection Jombang - Ino Angga Putra; Muhamad Habib Fahrizal; Khotim Fadhli (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The purpose of the study was to determine the strategy for developing MSMEs based on the creative economy by Faiz Convection and to find out the results achieved from the development of MSMEs based on the creative economy by Faiz Convection. This study uses a qualitative descriptive method which aims to analyze the data by describing or providing an objective description of the actual state. The place of this research was carried out in Faiz Convection Jombang. The data used are primary and secondary data. Collecting data through activities, namely a) observation on the object of research, b) interviews with sources with interview instruments, c) documentation in the form of writing or pictures, and d) literature review for the purposes of preparing reports. The data processing of the results of this study used a qualitative descriptive analysis tool. The results obtained indicate that the creative economy-based MSME development strategy in faiz convection is carried out by developing a marketing system and product development by making new breakthroughs regarding the variety of clothing models produced and innovation. System development at the convection faiz by conducting briefings to owners and employees in completing all work at the production site so that it runs effectively and efficiently.